Analyzing frequency and distributional pattern of discourse markers in the Malaysian newspaper - Mohan Rathakrishnan, Hafizah Hajimia, Manvender Kaur Sarjit Singh, (Opción, 1970)
Numerous studies showed a discourse marker is a confusing marker and when it is related to various genre, deems necessary for a thorough study. Thus, frequency and distributional patterns of DMs would be able to clear this confusion. The frequency and the pattern of discourse markers „and‟ were examined to see the usage of discourse markers between the sentences and the articles of the news report by applying the corpus tools. The result indicated that different grammatical word classes of discourse markers „and‟ exist in the articles and various positions of DMs „and‟ was identified based on its distributional patterns.